Health in the 5th 5-years Development Plan of Iran: Main Challenges, General Policies and Strategies - N Rostamigooran; MH Salarianzedeh; S Alikhani; B Damari; A Vosoogh Moghaddam; A Delavari; B Larijani (Tehran University of Medical Sciences, 2013)
Access to the right to the highest attainable level of health is a constitutional right that obliges governments and other players to take step to increase all individuals' chances of obtaining good health. At the least, health and education are two crucial requirements for this as well. Iran's vision 2025 is going to lead the country to a developed state with the highest rank of economic, scientific and technological status in the region. Enjoying health, welfare, food security, social security, equal opportunities, etc, are also considered as part of characteristics of Iranian society in 2025. Although health system of Iran has many achievements in providing health services specially for the poor following the Islamic Revolution of 1979, but the evidences gathered to develop the 5th 5-years economical, social and cultural plan (5th5YDP:2011-2015), listed a variety of main challenges in stewardship, financing, resources generation and service provision functions of the existing health system. Thus, to overcome the main challenges, about 11% of general policies of 5th5YDP are directly address health related issues with emphasizing on healthy human and comprehensive health approach with considering: Integration of policy making, planning, evaluation, supervision and public financing; Developing both quantity and quality of health insurance system and reducing out-of-pocket expenditures for health services to 30% by the end of the 5th plan. The strategies of 5th5YDP adopted by the parliament as an Act will change the health system fundamentally through tuning the main drivers; so, its implementation needs brave leaders, capable managers, motivated technical staff and social mobilization.